PENDAMPINGAN UMKM KERIPIK TEMPE DESA LANGSE KECAMATAN MARGOREJO DALAM MENDESAIN LABEL PRODUK - Daniel Alfa Puryono; Listiarini Edy Sudiati; Ninik Haryanti (Fakultas Teknik Universitas Diponegoro, 2022)
One of the impacts of the Covid-19 pandemic is restrictions on large-scale gatherings. In fact, as a seller, it is very important to do marketing to introduce their products. Moreover, the marketing carried out by the tempe chips SMEs from Langse Village residents is still by word of mouth and left in the stalls. Because they feel that the resulting product is still simple, the packaging is unattractive and does not yet have a name, let alone a competitive brand or design. Whereas the role of label design is very important, because it can create a first impression even before the product is consumed. Labels have supported the creation of added value for a product in terms of shape, color, and graphics. Labels also function in building the identity of a product. This community service activity in Langse Village, Margorejo District has the aim of training and helping the community. Especially the tempe chips SME owners in making graphic designs, namely making product labels using the CorelDraw application. The expected benefit is that it will create increased marketing and product purchases through more attractive label designs. This activity was carried out in 3 stages, namely the first stage to get the perceptions and expectations of MSMEs on the label design that they wanted to produce for products by filling in the data and followed by the introduction of the Coreldraw application. The second stage is the process of making the label design for the tempe chips product and in the third stage the improvement of the label design and how to print it is carried out. After being given assistance and training on designing product labels, the Langse Village MSMEs can practice it in their business and in the future can consult directly with STMIK AKI Pati in promoting and selling their products. Although it is still at the basic stage of the training provided, it is hoped that the results of the training can be developed independently. Because product labels play an important role in product promotion and introduction to consumers and can increase the selling value of the product. In addition, consumers will also find it easier to find information about these products.Kata kunci : Graphic Design, Product Label, MSME, Coreldraw